Islamic Education Management and the Challenges of Multiculturalism at Environment STAI Al-Furqan Makassar - Sandi Sandi; Akmal Akmal; Andi Nurmaedah Mustari; Ismail Ismail (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research aims to analyze the implementation of Islamic education management and the challenges of multiculturalism at STAI Al-Furqan Makassar. Employing a qualitative approach with a case study design, data were collected through interviews, observations, and documentation, and then analyzed thematically. The research findings indicate that education management at this campus has been implemented in a structured manner with Islamic principles such as justice, deliberation, and responsibility. In a multicultural context, the campus faces challenges in the form of cultural conflicts, differences in religious practices, and communication gaps. However, through religious moderation strategies, student organization development, and anti-discrimination policies, diversity has been successfully managed into an integrative strength. Adaptive and inclusive Islamic education management has proven to contribute to creating a harmonious campus atmosphere and improving the quality of education both spiritually and intellectually